2018
DOI: 10.1038/s41598-018-30549-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of hydration energy and co-ions association on monovalent and divalent cations adsorption at mica-aqueous interface

Abstract: Adsorption of ions at the solid - aqueous interface is the primary mechanism in fast biological processes to very slow geological transformations. Despite, little is known about role of ion charge, hydration energy and hydration structure on competitive adsorption of ions, their structure and coverage at the interface. In this report, we investigate the structure and adsorption behavior of monovalent (Rb+ and Na+) and divalent (Sr2+ and Mg2+) cations ranging from 0–4.5 M of bulk concentrations on the muscovite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 60 publications
7
46
2
Order By: Relevance
“…42,44,59 The layering extends to about 10 Å into the liquid, which is in excellent agreement with that seen in earlier work. 42,44,59 Fig. 3(c) shows that the water adjacent to the surface with potassium is less well ordered, but the weak layering extends a similar distance into the liquid.…”
Section: Mica-water Interfacesupporting
confidence: 91%
See 2 more Smart Citations
“…42,44,59 The layering extends to about 10 Å into the liquid, which is in excellent agreement with that seen in earlier work. 42,44,59 Fig. 3(c) shows that the water adjacent to the surface with potassium is less well ordered, but the weak layering extends a similar distance into the liquid.…”
Section: Mica-water Interfacesupporting
confidence: 91%
“…3(d), the peak labelled P 1 has been reported in other work as the 'adsorption layer', while the peak labelled P 2 is referred to as the 'hydration layer'. 42,44,59 The distance between the two peaks is 2.8 Å, which is larger than the value of 1.2 Å estimated in previous work using high-resolution specular X-ray reflectivity, and Monte Carlo and MD simulations. 42,44,59 The layering extends to about 10 Å into the liquid, which is in excellent agreement with that seen in earlier work.…”
Section: Mica-water Interfacecontrasting
confidence: 63%
See 1 more Smart Citation
“…The properties of water are expected to remain constant, and typical of a liquid water, from the first nanometer onwards (e.g. [11,12,13]).…”
Section: The Extended Generalized Effective Stress Conceptmentioning
confidence: 99%
“…It was found that both ions and water molecules exhibit a layerlike structure in the direction perpendicular to the interface. 15,1731 Besides, the water molecules 1921,2426,28,30,32 and ions 14,19,20,24,25,28,30,32,33 at the interface are laterally ordered with respect to the crystal structure. The dipole moment of water molecules at the SLI also tends to be ordered.…”
Section: Introductionmentioning
confidence: 99%